SOCIAL CAPITAL, SUPPORT NETWORKS AND BLACK ELDERLY PERSONS - Howes, Francis (Social Work/Maatskaplike Werk, 2007)
The Department of Social Services and Poverty Alleviation in the Western Cape sees itself as the lead Department for social capital formation. (Department of Social Services and Poverty Alleviation, 2005:5). The said Department accepts the following definition of social capital: “Social capital refers to the strengthening and establishment or networks, relationships, norms and values that contribute to the building of social cohesion, racial integration and the strengthening of a social safety net during times of crisis (economic, natural and other). It is not an end in itself, but a means to an end” (Department of Social Services and Poverty Alleviation, 2005:23). Putnam (2000:19) makes the following statement: “social capital refers to connections among individuals – social networks and the norms of reciprocity and trustworthiness that arises from them. In that sense social capital is closely related to what some have called ‘civic virtue’. The difference is that ‘social capital’ calls attention to the fact that civic virtue is most powerful when embedded in a dense network of reciprocal social relations. A society of many virtuous but isolated individuals is not necessarily rich in social capital.” Social capital is thus of pivotal importance in the provincial and national agenda of fostering social cohesion and social inclusiveness.